Postnatal women's perspectives on the feasibility of introducing postpartum home visits: a Jordanian study. Issue 3 (3rd July 2018) - Shaban, Insaf A.; Al-Awamreh, Khetam; Mohammad, Khitam; Gharaibeh, Huda
ABSTRACT: In Jordan, there is a deficiency in postnatal care provided to women and their newborns. This study investigated the feasibility of initiating postnatal home visits in Jordan. Thirty Jordanian mothers who had recently given birth were recruited from two governmental hospitals in the northern region of Jordan to participate in a qualitative study through face-to-face, voice-recorded interviews. The findings revealed that initiating postnatal home visits as part of postnatal care was well-received by the participants. Mothers' views and perceptions regarding postpartum home visits play an integral role in finding areas to improve postnatal services.